Long-Term Food Choice and Weight Loss on a Mobile Program With Food Color System. (7th June 2021) - Mitchell, Ellen; Yang, Qiuchen; Behr, Heather; Ho, Annabell; DeLuca, Laura; May, Christine; Michaelides, Andreas
Abstract: Objectives: It is unclear if individuals sustain healthy food choices long-term on a mobile, self-directed weight loss program, or how those choices influence weight loss. We examined differences in food choice and dietary quality by weight lost at 18 months on a mobile behavior change weight loss program with a traffic light food system designed to encourage healthier eating behaviors. We expected that users with greater amounts of weight loss would show healthier food choices and dietary quality. Methods: On the program, users are encouraged to consume a ratio of 30% green (low-calorie, high-volume, nutrient-rich foods), 45% yellow, and 25% red (high-calorie, low-volume) foods. They are also provided information on behavior change principles. We evaluated food ratios and self-reported dietary quality in 148 adults 18 months after starting the program with a retrospective cohort design. Food ratios were measured via food intake self-reported on the program. Dietary quality was measured using a validated questionnaire assessing adherence to the Dietary Approaches to Stop Hypertension (DASH) diet (DASH-Q). Respondents were categorized into high (>10%, n = 71), moderate (5–10%, n = 35), and low or no (<5%, n = 42) weight loss groups based on weight lost by 18 months. ANOVAs tested differences in food ratios and dietary quality between groups. Results: Baseline BMI did not differ between weight loss groups (high: 36.9, moderate: 36.0, low: 36.5; P = 0.68). However, there were significant differences in green food ratios across weight loss groups for breakfast (high: 37%, moderate: 37%, low: 34%; P = .02), lunch (29%, 27%, 25%; P < .001), and dinner (22%, 20%, 16%; P < .001). Red food ratios also differed across groups for breakfast (21%, 27%, 26%; P < .001), lunch (34%, 35%, 37%; P < .002), and dinner (36%, 39%, 43%; P < .001). The weight loss groups also differed in DASH dietary pattern scores (high: 41.79, moderate: 42.52, low: 36.95; P = .02). Conclusions: Users with greater weight loss ate more green foods, fewer red foods, and adhered more to the DASH diet than users with less weight loss. These differences were apparent even 18 months later. This highlights the role of food choice and dietary quality in weight loss and suggests that a mobile behavior change program with a traffic light system could aid in healthier long-term dietary consumption. Funding Sources: This study was funded by Noom Inc.